2018
DOI: 10.1111/febs.14621
|View full text |Cite
|
Sign up to set email alerts
|

The extended cytoplasmic tail of the human B4GALNT2 is critical for its Golgi targeting and post‐Golgi sorting

Abstract: The proteins β1,4GalNAcT II, β1,4-GalT1, FucT I, FucT VI and ST3Gal IV are noted B4GALNT2, B4GALT1, FUT1, FUT6 and ST3GAL4, whereas the corresponding human genes are noted B4GALNT2, B4GALT1, FUT1, FUT6 and ST3GAL4 according to the HUGO nomenclature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…Transcription of the B4GALNT2 gene generates at least two different transcripts that only differ in the first exon. These two transcripts contain a translational start site, from which two different transmembrane polypeptides originate: one, referred to as "long form", contains an unusually 2 of 18 long cytoplasmic tail [5,6]; the second, known as "short form", is provided with a cytoplasmic tail of conventional length [7]. Previous studies have shown a higher enzymatic activity of the short form compared with the long form [8].…”
Section: Introductionmentioning
confidence: 99%
“…Transcription of the B4GALNT2 gene generates at least two different transcripts that only differ in the first exon. These two transcripts contain a translational start site, from which two different transmembrane polypeptides originate: one, referred to as "long form", contains an unusually 2 of 18 long cytoplasmic tail [5,6]; the second, known as "short form", is provided with a cytoplasmic tail of conventional length [7]. Previous studies have shown a higher enzymatic activity of the short form compared with the long form [8].…”
Section: Introductionmentioning
confidence: 99%
“…Both transcripts contain a translational start site from which two different transmembrane polypeptides originate: the one referred to as “long form” contains an exceptionally long cytoplasmic tail, while the one referred to as “short form” contains a cytoplasmic domain of conventional length [ 15 , 16 ]. Both forms localize mainly in the Golgi, although the long form exhibits also post-Golgi localizations [ 20 ]. B4GALNT2 is expressed at a very high level in normal colon but undergoes a dramatic down-regulation in CRC [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both isoforms display Golgi localization, although the long form is present also in post-Golgi vesicles and the plasma membrane [ 25 ]. The short form appears to be enzymatically more active than the long form [ 26 ] and is by far the dominant form in both normal and cancer colon [ 27 ].…”
Section: The Sd a Antigen: Structure And Biosynthesismentioning
confidence: 99%